Má oclusão em pré-escolares: uma análise do SB Brasil 2010 - Daniella Borges Machado (2013)
Aim: identify factors associated with the prevalence of anterior open bite among five year old Brazilian children. Methods: a cross-sectional analytical study was undertaken using data from the National Survey of Oral Health (SB Brasil 2010). The outcome variable was anterior open bite, which was classified as present or absent. The independent variables were classified by individual, and by sociodemographic and clinical factors. Data was analyzed through bivariate and multivariate analysis using the SPSS statistical program (version 18.0) with a 95% level of significance. Results: the prevalence of anterior open bite among the children was 12.1%. Multivariate analysis showed that pre-school children living in the South region of Brazil had an increased chance of 1.8 times of having anterior open bite. Children identified with alteration in overjet had a 14.6 times greater chance of having anterior open bite. Conclusion: there was a significant association between anterior open bite and the region of Brazil where the children lived and alteration in overjet.